ANTIBACTERIAL TEST OF PANGIUM (Pangium edule Reinw) EXTRACT AGAINST THE GROWTH OF FISH SPOILAGE BACTERIA - Endang Sri Heruwati; Lily lsmaini; Wibowo Mangunwardoyo (Indonesian Fisheries Research Journal, 2009)
An antibacterial test was conducted on fresh and fermented Pangium edule Reinw. Seed extracts against gram positive and negative spoilage bacteria associated with fish.